Reflecting with God: Connecting Faith and Daily Life in Small Groups - Johnson, Abigail (Rowman & Littlefield Publishers, 2004)
Untangling the day-to-day issues in our multifaceted lives can seem daunting. Time to sit quietly and reflect is rare. If we are fortunate, we have good friends or close family members with whom to talk things through and find clarity, but many times we feel isolated and lonely. As people of faith, we add another layer to our reflections when we wonder where God fits into our lives. In a broad sense, theological reflection happens any time that we wonder about God, our faith, our beliefs, and our values. In this book, however, Abigail Johnson offers a structured process for engaging in theological reflection by looking at a situation or event through a series of questions. These questions are designed to help individuals and small groups think through situations with the eyes of faith. Johnson provides detailed instructions for group facilitators, making this book a valuable resource for any theological reflection leader. She demonstrates how theological reflection will enrich the faith life of the individual and increase group members’ sense of belonging to God and to the whole people of God. She also shows how small groups engaging in theological reflection affects the ongoing life of a congregation—particularly in the community’s worship and the members’ practice of spiritual disciplines.